Epistemic democracy and the quality of government. Issue 1 (1st January 2019) - Rothstein, Bo
ABSTRACT: Epistemic democracy implies that in order for democratic decisions to be legitimate, it is no enough that they are taken according to established democratic procedures. In addition, epistemic democracy demands that two additional demands should be fulfilled, namely that the decisions produced by a democratic process also are 'fair' and 'true'. The fairness demand is in this article connected to the principle of human rights while the 'true' demand related to the propensity of representative democracy to produce outcomes that increases human well-being. Empirical research shows that representative democracy without a high quality of the institutions responsible for implementing public policies do not deliver increased human well-being. A special problem is that representative democracy has not turned out to be a safe cure against endemic corruption. The 'quality of government' factor thus implies control of corruption and also the rule of law and competence in the public administration. It is argued that meritocracy in the recruitment and promotion to positions in the public administration can serve to increase both the level of 'fairness' and the level of 'truth' in democracies.